The 'Education of Public Opinion' and the 'Criticism of Government Policy' : a social utility examination of political speech rights and Irish democracy under Articles 6.1 and 40.6.1 - Kavanagh, Jennifer Margaret (Trinity College (Dublin, Ireland). School of Law, 2015)
This thesis represents a socio-legal exploration of the relationship between political speech rights and democracy in Ireland. In particular, the thesis focuses on the ability of citizens to exercise their right to 'criticise government policy' under Article 40.6.1 (i) when the direct and indirect restrictions on political speech are considered. This thesis will also consider how the role of citizens under Article 6.1 is affected when these restrictions are analysed.
Embargo End Date: 2023-08-01
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin, 2015